2019
DOI: 10.1111/adb.12792
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned aversive memory associated with morphine withdrawal increases brain‐derived neurotrophic factor in dentate gyrus and basolateral amygdala

Abstract: Morphine has been shown to increase the expression of brain‐derived neurotrophic factor (BDNF) in the brain. However, little is known about the effect of conditioned naloxone‐precipitated morphine withdrawal on BDNF and its precursor protein, proBDNF. We used the conditioned place aversion (CPA) paradigm to evaluate the role of corticotropin‐releasing factor (CRF)/CRF1 receptor signaling on the BDNF expression and corticosterone plasma levels after CPA expression and extinction. Male mice were rendered depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…The role of amygdalar BDNF in extinction of addictive behaviors is understudied, though it may be regulating aversive responses to withdrawal ( Heldt et al, 2014 ). Yet, opposing effects were reported for alcohol and opioids; having decreased BDNF in AMY during alcohol withdrawal ( You et al, 2014 ), but an increase during morphine-induced withdrawal ( Martínez-Laorden et al, 2020 ). However, decreased BDNF expression in alcohol withdrawal might be due to the absence of an extinction phase.…”
Section: Discussionmentioning
confidence: 99%
“…The role of amygdalar BDNF in extinction of addictive behaviors is understudied, though it may be regulating aversive responses to withdrawal ( Heldt et al, 2014 ). Yet, opposing effects were reported for alcohol and opioids; having decreased BDNF in AMY during alcohol withdrawal ( You et al, 2014 ), but an increase during morphine-induced withdrawal ( Martínez-Laorden et al, 2020 ). However, decreased BDNF expression in alcohol withdrawal might be due to the absence of an extinction phase.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we collected the brain tissue at 6 h after the last morphine injection to avoid the acute effect of single morphine exposure (the half‐life of morphine is 2–4 h) and the effect of long‐term abstinence (>24 h)‐induced emotional and mental symptoms. Third, our work focused on the hippocampal DG, which is not one of the traditional members of the reward system like LC, NAc, VTA, PFC, and hippocampal CA1, 1,21,30 but increasing evidence has shown that the DG is not only involved in morphine‐associated memory but also in morphine dependence 11–15 …”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Moreover, recent studies reveal that the DG is activated in morphine-dependent rodents. [11][12][13][14][15] Rats receiving 10 days successive increasing doses of morphine treatment display an evident c-fos induction in the DG. 15 Brain imaging research in rats shows that Meng Jia and Xuewei Wang contributed equally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation